Macroeconomic cost of excluding persons with disabilities from the workforce in Spain - Angeles Cámara; María Isabel Martínez Martín; Rosa Santero Sánchez (IZA Journal of Labor Policy, 2020)
The article analyzes and deals with the problems associated to exclusion of persons with disabilities from the workforce based on the impact it has in the context of economic and social dimensions, considering the fact that it results in high cost because of such exclusion. Specifically, it estimates the macroeconomic cost to the Spanish economy by modeling the incorporation of this collective into the job market. Varying types of inclusion are proposed, which are defined in terms of the different barriers that this collective encounters when attempting to access the job market. In this article, these barriers are divided between those that result from a labor gap and those that result from an education gap. The study then quantifies the macroeconomic benefits resulting from an increased participation of persons with disabilities in the workforce.
Keywords: J15; J18; J71; J78; C67; 330; integration; macroeconomic costs; persons with disabilities; workforce exclusion